Red blood cell triglycerides—a unique pool that incorporates plasma-free fatty acids and relates to metabolic health - Song, Yilin; Jensen, Michael D. (Journal of lipid research, 2021)
Most research into red blood cell (RBC) lipids focuses on membrane phospholipids and their relationships to metabolic conditions and diet. Triglycerides (TGs) exist in most cells; the TG-fatty acids serve as readily available fuel for oxidative phosphorylation. Because RBCs lack mitochondria, they would not be expected to store fatty acids in TG. We followed up on a previous in vitro study that found FFA can be incorporated into RBC-TG by testing whether intravenously infused [U-13C]palmitate could be detected in RBC-TG. We also quantified RBC-TG fatty acid concentrations and profiles as they relate to plasma FFA and lipid concentrations. We found that 1) RBC-TG concentrations measured by glycerol and LC/MS were correlated (r = 0.77; P < 0.001) and averaged <50 nmol/ml RBC; 2) RBC-TG concentrations were stable over 18 h; 3) [U-13C]palmitate was detectable in RBC-TG from half the participants; 4) RBC-TGs were enriched in saturated fatty acids and depleted in unsaturated fatty acid compared with plasma FFA and previously reported RBC membrane phospholipids; 5) RBC-TG fatty acid profiles differed significantly between obese and nonobese adults; 6) weight loss altered the RBC-TG fatty acid profile in the obese group; and 7) the RBC-TG fatty acid composition correlated with plasma lipid concentrations. This is the first report showing that plasma FFA contributes to RBC-TG in vivo, in humans, and that the RBC-TG fatty acid profile is related to metabolic health. The storage of saturated fatty acids in RBC-TG stands in stark contrast to the highly unsaturated profile reported in RBC membrane phospholipids.